2012
DOI: 10.3399/bjgp12x630061
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic identification of depression in young people: lessons fromthe introduction of a new technique in general practice

Abstract: BackgroundMild-to-moderate depression in young people is associated with impaired social functioning and high rates of affective disorder in adult life. Earlier recognition of depression in young people has the potential to reduce the burden of depression in adulthood. However, depression in teenagers is underdiagnosed and undertreated. AimTo assess the usability and usefulness of a cognitive-behavioural-therapy-based technique for Therapeutic Identification of Depression in Young people (TIDY). Design and set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…A quest for certainty in areas of complex practice, especially when it concerns individual experiences, can be counterproductive and scholars have cautioned against clinging to the ‘shelter of diagnosis’15 when what is required involves attention to alleviating suffering and working purposefully with patients to catalyse their own creative capacity 14. Iliffe et al 's32 33 earlier cited work demonstrated that when GPs were fixed on the concept of depression as disease, they were uncomfortable talking to young people.…”
Section: Discussionmentioning
confidence: 99%
“…A quest for certainty in areas of complex practice, especially when it concerns individual experiences, can be counterproductive and scholars have cautioned against clinging to the ‘shelter of diagnosis’15 when what is required involves attention to alleviating suffering and working purposefully with patients to catalyse their own creative capacity 14. Iliffe et al 's32 33 earlier cited work demonstrated that when GPs were fixed on the concept of depression as disease, they were uncomfortable talking to young people.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31] Internationally produced work also reports GPs' reluctance to ask questions about emotional distress, which leads to lost opportunities to support wellbeing. 7,15 GPs describe anxiety and uncertainty about how best to respond to adolescent psychological difficulties, 24 and differ in their degree of engagement with troubled teenagers.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Illiffe and colleagues report GPs being 'uncomfortable' diagnosing depression, 15 and not wanting 'to medicalise psychological distress'. 16 This article presents a qualitative study exploring GPs' experiences and perceptions of consulting with adolescents who present with psychological difficulties. It builds on an earlier first level of analysis which concluded that professional anxiety and uncertainty about practice dominate consultations in this arena.…”
Section: Introductionmentioning
confidence: 99%